The Association between Weather Variability and Dengue Hemorrhagic Fever in Tegal Regency - Fitra Tresna Asih Arieskha; Mursid Rahardjo; Tri Joko (Universitas Airlangga, 2019)
Dengue Hemorrhagic Fever (DHF) was a vector-borne disease that spreads rapidly and could cause death. Weather changes and climate change indirectly affects the incidence of dengue hemorrhagic fever. Conducive tropical weather and climate elements such as rainfall, air temperature and air humidity that are supported by the existence of habitat for Aedes aegypti mosquito could increase the risk of dengue cases. The purpose of this study was to determine the relationship between weather variability and the incidence of DHF in Tegal Regency during the period of 2012-2018. The design of this study was ecological study whereas unit analysis of the study is at population level. The data obtained was analysed by using correlation test spearman to identify correlation of the moran index on weather variability and dengue morbidity rates. The results of variability analysis were rainfall (p = 0,879; r = 0,071), air temperature (p = 0,023; r = -0,821) and air humidity (p = 0,879; r = -0,071). It was showed that the significant risk factors for the incidence of DHF in Tegal Regency was air temperatures. The study concluded that Tegal Regency has weather variability conditions that have the potential to increase the chances of dengue fever therefore intervention such as mitigation are expected to stifle the pace of climate change, and adaptation are needed to facing future impacts that related to the eradication of DHF.